The ConNECT approach: toward a comprehensive understanding of meaningful interpersonal moments in psychotherapy and beyond - Kaiser, Niclas; Avendano-Diaz, Juan Camilo (Frontiers in Human Neuroscience, 2025)
Relational neuroscience struggles to capture the complex dynamics of shared interpersonal moments, leading to gaps in understanding whether and how interdependencies between interacting persons translate into something meaningful. Current neuroscientific research often focuses on motor synchronization and cognition rather than the implicit relational qualities central to psychotherapy. We argue that this disconnect stems from an over-reliance on simplified quantitative methods, a failure to centralize experiential factors, and the lack of Convergence research. Drawing on emerging frameworks such as 4E cognition (embodied, enacted, extended, and embedded) and MoBI (Mobile Brain/Body Imaging), we advocate for integrating subjective and experiential elements with neural data. We propose focusing on “qualities” in multi-brain neuroscience—moving beyond binary or linear scales—to better capture the subtleties of relational moments. Finally, we emphasize the importance of convergence research across disciplines to better understand what interpresence holds. If psychotherapeutic knowledge is used to guide neuroscientists in what to look for, this multi-disciplinary approach holds promise for advancing the study of psychotherapy’s relational processes, offering new insights into the neurobiology of meaningful moments in therapy and elsewhere. We propose ConNECT (Convergence research including Neuroscience and Experiences, Capturing meaningful dynamics with Therapists’ knowledge) as the path forward.